An Analysis of Registered Clinical Trials in Otolaryngology from 2007 to 2010: ClinicalTrials.gov - Witsell, David L. (2013)
OBJECTIVE: To describe the conditions studied, interventions used, study characteristics, and funding sources of otolaryngology clinical trials from the ClinicalTrials.gov database; compare this otolaryngology cohort of interventional studies to clinical visits in a health care system; and assess agreement between clinical trials and clinical activity. STUDY DESIGN: Database analysis. SETTING: Trial registration data downloaded from Clinical Trials.gov and administrative data from the Duke University Medical Center from October 1, 2007 to September 27, 2010. METHODS: Data extraction from ClinicalTrials.gov was done using MeSH and non-MeSH disease condition terms. Studies were subcategorized to create the following groupings for descriptive analysis: ear, nose, allergy, voice, sleep, head and neck cancer, thyroid, and throat. Duke Health System visits were queried by using selected ICD-9 codes for otolaryngology and non-otolaryngology providers. Visits were grouped similarly to ClinicalTrials.gov for further analysis. Chi-square tests were used to explore differences between groups. RESULTS: A total of 1115 of 40,970 registered interventional trials were assigned to otolaryngology. Head and neck cancer trials predominated. Study models most frequently incorporated parallel design (54.6%), 2 study groups (46.6%), and randomization (69.1%). Phase 2 or 3 studies constituted 46.4% of the cohort. Comparison of the ClinicalTrials.gov database with administrative health system visit data by disease condition showed discordance between national research activity and clinical visit volume for patients with otolaryngology complaints. CONCLUSIONS: Analysis of otolaryngology-related clinical research as listed in ClinicalTrials.gov can inform patients, physicians, and policy makers about research focus areas. The relative burden of otolaryngology-associated conditions in our tertiary health system exceeds research activity within the field.